The Diagnostic Workup, Screening, and Treatment Approaches for Patients with Delusional Infestation - Skyler Coetzee; Chandrally Mahajan; Katlein França (Adis, Springer Healthcare, 2023)
Abstract Delusional infestation (DI) is a psychiatric disorder defined by the fixed, false belief that one has been infested by an organism without evidence to support this. Patients may present with skin lesions and report abnormal cutaneous sensations. The diagnostic workup for patients presenting with delusional infestation is essential to ensuring accurate diagnosis in ruling out other explanations for symptoms and investigating potential secondary causes of DI. In addition to a comprehensive history and physical examination, laboratory workup should be considered depending on the clinical picture. Antipsychotic medications are the most common drugs used in management of adults with DI and tailor the choice of treatment according to patient characteristics. This article serves as a guide for dermatologists, psychiatrists, and other clinicians as it reviews the workup and screening that should be considered when managing a patient with delusional infestation and subsequent treatment protocols once the diagnosis has been made.